Analisis Kinerja Perusahaan Produk Kopi Melalui Pendekatan Rasio Produksi - Heri Wibowo (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
The company of coffee product was claimed always to serve of customer need by qualityoutput product better, because the output product was exported. To know the company performancewas by doing the survey about variables and then account the production cost efficiency by productionratio method. The result during 2005 -2010 was the multiple regression that the variables is the mostinfluence of job satisfaction employees was reward and recognition with the coefficient was 0,509 or50,9%. By the T test is known that reward and recognition variable was influenced partially to the jobsatisfaction employees with thitung X1 (3,529) > ttabel (2,03951) and probability (0,001) > alpha (0,05)and the result of production ratio was more low of production ratio, it was more big profit thecompany. Based on research, the most dominant variable was reward and recognition, and the mostefficient of production ratio was 0,018 or 18% in 2010Keywords: Production Ratio